Determinants of Financial Performance of Business Ecosystems in Russia - Lukin Ivan (Journal of Corporate Finance Research / Корпоративные Финансы | ISSN: 2073-0438, 2024)
The scientific literature provides a comprehensive description of business ecosystems and their key advantages. However, there is a lack of thorough exploration into the practicality and efficacy of implementing business ecosystems, as well as strategies to enhance their economic impact. This study examines the impact of three key factors on the effectiveness of business ecosystems: ecosystem self sufficiency, service integration, and customer satisfaction. A sensitivity analysis of the Net Present Value (NPV) of ecosystems was conducted using discounted cash flow models for two leading Russian technology companies, IC PJSC Yandex and IC PJSC VK. The analysis focused on key drivers such as the number of active clients, average customer churn rate, digital sales funnel, and average transaction value. Ecosystem self-sufficiency significantly and variably affects NPV, with the removal of even a single business line leading to a negative impact on ecosystem value (ranging from –5 to –167%). The level of service integration has a minor influence on ecosystem NPV, with a 50% variance in subscription users leading to an NPV deviation of no more than 16%. Customer satisfaction, however, can have a substantial positive effect on ecosystem NPV, with a 1% improvement in satisfaction leading to a potential 3.7% increase in NPV. From the point of view of scientific novelty, this study allows to conclude that each factor of the effectiveness of ecosystem implementation is associated with the ability to collect and use information. For the Russian technology sector, a significant impact was identified in two of the three key factors: ecosystem self-sufficiency and customer satisfaction. The practical significance of the results of this study lies in determining the general factors that show under what conditions the introduction of an ecosystem is economically justified for the technology sector.